Relationship between environmental regulation and the volume of import in OECD countries - Norazean Rasit; Sarma Imran Aralas (Faculty of Business, Economics and Accountancy, 2021)
The Pollution Haven Hypothesis (PHH) is now the concern of various parties. The migration and growth of dirty industries will cause the occurrence of massive pollution resulting in the occurrence of unlimited environmental pollution that will affect not only human health, but also the economic activities of a country that needs to be emphasized. Therefore, this study examines the relationship between environmental regulation and the volume of imports whether the migration of developed countries to developing countries or third countries occurs to the destination country or vice versa. By using panel data, involving OECD countries from 2002 to 2020 and the fixed effect test applied, the results indicate that there has a negative relationship between the volume of imports and environmental regulation. The study proves that environmental regulation is influenced by the volume of imports. It can be concluded that there is the existence of PHH in OECD countries. By tightening the environmental laws will be able to prevent excessive pollution.